Insulin sensitivity in male sheep born to ewes treated with testosterone during pregnancy. (14th June 2021) - Carrasco, Albert; Recabarren, Mónica P.; Rojas-García, Pedro P.; Silva, Nelson; Fuenzalida, Jonathan; Sir-Petermann, Teresa; Recabarren, Sergio E.
Abstract: In animal models, exposure to excess testosterone during gestation induces polycystic ovary syndrome (PCOS)-like reproductive and metabolic traits in female offspring, suggesting that the hyperandrogenemic intrauterine environment may have a role in the etiology of PCOS. Additionally, few studies have also addressed metabolic and reproductive outcomes in male offspring. In the present study, the intravenous glucose tolerance test (IGTT) was used to assess the insulin–glucose homeostasis at various ages during sexual development in male sheep born to testosterone-treated ewes. To further analyze the programming effect of testosterone on insulin–glucose homeostasis, indexes of insulin sensitivity were assessed in orchidectomized post-pubertal males born to testosterone-treated ewes (Torq-males) and orchidectomized post-puberal controls (Corq-males) before and 48 h after a testosterone injection. There was no difference in insulin sensitivity indexes between males born to testosterone-treated ewes (T-males) and control males born to control ewes (C-males) at 5, 10, 20 and 30 weeks of age, representing the infantile, early and late pre-pubertal, and early post-pubertal stage of sexual development, respectively. In orchidectomized males, basal levels of insulin and glucose were not different between both groups before and after the testosterone injection; however, Torq-males released more insulin before and after T challenge during the first 20 min of the test. Despite this, plasma glucose concentrations were not different in both groups during IVGTT, resulting in an insulin sensitivity index composite similar between groups. We concluded that the effect of prenatal exposure to excess testosterone may reprogram the pancreatic β-cells insulin release in ovine males, with effects more evident in castrated males versus intact males.